Informal Workplace Learning in Austrian Banks: The Influence of Learning Approach, Leadership Style, and Organizational Learning Culture on Managers' Learning Outcomes. (March 2014) - Froehlich, Dominik; Segers, Mien; Van den Bossche, Piet
Abstract Informal workplace learning takes an increasingly focal role in human resource development (HRD) practice and research, as it contributes to or ganizations' adaptability and competitiveness. However, little is known about how individual managers' approaches to learning and contextual influences such as leadership and organizational learning culture influence learning outcomes. This study narrows these gaps by examining the relationship between learning approaches, experienced leadership style, organizational learning culture, and learning outcomes among 143 Austrian bank managers in a cross‐sectional, quantitative questionnaire study. Results show that the choice of learning approach significantly affects several conceptualizations of learning outcome. Moreover, we have found that learning approaches partially mediate the effects of experienced leadership style on learning outcomes. Also, organizational learning culture moderates the effects of leadership style and learning approaches. These findings call for further research of the process and outcome of informal workplace learning and imply a need for greater awareness of both individuals' learning approaches and contextual influences of the learning process in practice.